WAYANG FOR ASSISTING STUDENTS IN MASTERING SPEAKING SKILLS IN SENIOR HIGH SCHOOL: RESEARCH AND DEVELOPMENT - Armedia Wiratama; Dian Fadhilawati; Miza Rahmatika Aini (JARES (Journal of Academic Research and Sciences), 2023)
ABSTRACT This research is a Research and Development adapted Sugiyono’s procedures which ssssss Potential and problem detection as well solution proposed, product design and development, experts’ validation and revision, targeted users’ responses, evaluation and revision, and final product and publication, This research is intended to develop Wayang as a medium for mastering speaking skills especially for assisting X-grade students in practicing storytelling as well as knowing the feasibility of the developed product and gaining targetetted users’ responses toward the developed product. The research subjects were 20 students and 5 English teachers from various senior high schools in Blitar Regency. The results of the study revealed that; (1) The developed storytelling model consists of 5 stories, 20 wayang characters, and 15 properties, equipped with 2 guidebooks for teachers and students. (2) The product (Wayang) which was developed as a learning medium is valid (87%) to be applied in speaking instruction, especially storytelling and (3) Students and teachers also presented positive responses toward wayang as a learning medium in speaking especially storytelling in which sshowed from the results of the questionnaire got 83% ( very Positive) from the students and 92% (Very positive) from the teachers. From the results above, it can be concluded that the developed storytelling with wayang is very valid and feasible to be applied as an alternative medium in learning to speak, especially storytelling in class X of Senior high school.